1991
DOI: 10.1007/bf00023272
|View full text |Cite
|
Sign up to set email alerts
|

Pre- and post-fertilization barriers to backcrossing the interspecific hybrid between Allium fistulosum L. and A. cepa L. with A. cepa

Abstract: To facilitate the introgression of desirable traits of Allium fistulosum into the genome of A . cepa, several accessions of the hybrid between these species were pollinated with A . cepa as the recurrent parent, and in vitro ovary and ovule culture were performed to obtain an increase in the recovery of backcross progeny . Compared to the results obtained from seed development in planta, the increase in the number of backcross progeny was generally very limited, and in some cases even a decrease was found . Ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

1997
1997
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 9 publications
0
17
0
Order By: Relevance
“…Pre-fertilization barriers in distant crosses, such as failure in pollen germination, slow pollen tube growth, or foreign pollen tube arrest in the style have been reported in different species (Kiełkowska & Adamus, 2006;Manickam & Sarkar, 1999b) including alliums (Gonzalez & Ford-Lloyd, 1987;Ohsumi et al, 1993;van der Valk et al, 1991a). Postfertilization barriers are related to abnormalities in the development of the zygote, absence or abnormal development of the endosperm which causes embryo starvation and abortion (Zenkteller, 1990).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Pre-fertilization barriers in distant crosses, such as failure in pollen germination, slow pollen tube growth, or foreign pollen tube arrest in the style have been reported in different species (Kiełkowska & Adamus, 2006;Manickam & Sarkar, 1999b) including alliums (Gonzalez & Ford-Lloyd, 1987;Ohsumi et al, 1993;van der Valk et al, 1991a). Postfertilization barriers are related to abnormalities in the development of the zygote, absence or abnormal development of the endosperm which causes embryo starvation and abortion (Zenkteller, 1990).…”
Section: Discussionmentioning
confidence: 99%
“…Cytological studies showed reproductive abnormalities in F1 hybrids and their progenies. Irregularities of chromosome pairing and occurrence of a range of structural changes in meiotic chromosomes resulted in unbalanced chromosome complements in the gametes, often causing lowered fertility or even sterility of the F 1 hybrids (Khush & Brar, 1992;Peffley, 1986;van der Valk et al, 1991a).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Unfortunately, subsequent backcrosses of the obtained F 1 A. cepa × A. fistulosum hybrids to A. cepa have proved problematic. The difficulties observed in genome transmission in advanced backcross generations have been explained by the sterility of F 1 A. cepa × A. fistulosum hybrids probably resulting from one of three possible mechanisms: stylar incongruity (van der Valk et al, 1991a), nuclear cytoplasmic incompatibility (Ulloa et al, 1995) or central cell nuclear cytoplasmic incongruity (Mangum and Peffley, 2005). Due to problems in introgression of Japanese bunching onion traits into onion, so far only four new varieties of A. fistulosum have been developed: Beltsville Bunching, Delta Giant, Top Onion and Wakegi Onion (Kik, 2002).…”
Section: Introductionmentioning
confidence: 99%